Symbolic expressions of Javanese culture: The Jaran Kepang dance of Temanggung as oral literature - Nugraheni, Molas Warsi; Andayani, Andayani; Eko Wardani, Nugraheni (Research Journal in Advanced Humanities, 2025)
The cultural values of Jaran Kepang are integral to understanding the Javanese philosophy of life. Anchored by such philosophical meanings, this study aims to uncover the symbolic meanings embedded in the Jaran Kepang dance. A qualitative descriptive approach with case studies was employed as the research method.  Data were collected through observation, interviews, literature analysis, and documentation. To interpret the symbols in this art form, the study utilized. Roland Barthes’ myth analysis framework. The study revealed that the choreography of Jaran Kepang portrays the valor and determination of soldiers in their struggle against enemies. This fighting spirit reflects the resilience and determination of Javanese society in facing life’s challenges. The accompanying music amplifies the soldiers’ fierce spirit, while the costumes symbolize themes of struggle, passion, loyalty, unity, and nationalism. Together, these elements encapsulate the cultural and philosophical essence of the Javanese way of life. This study contributes to cultural preservation, semiotic analysis, and character education by examining how the performance expresses Javanese values and can be used to teach moral lessons.